Determination of Irrigation water requirement and Scheduling of onion at Low land area of Wag-himra, Northern Ethiopia - Adane, messay Abera; Beza, Gashaw; Wale, Aemro (International Journal on Food, Agriculture and Natural Resources, 2023)
Irrigation that saves water is important for satisfying the economic and environmental sustainability of commercial agriculture and improving the living standard of the people. Precision irrigation scheduling is critical to improving irrigation efficiency.  A field experiment was conducted in two consecutive years at Abergelle irrigation schemes. The aim of the study was to determine crop water requirement and irrigation schedule of onion (when and how much to irrigate) for most market-oriented crops. The treatments were arranged with a factorial arrangement randomized complete block design with three replications. Three Levels of CROPWAT, fixed application depth (125%, 100%, and 75%ETc) and, three irrigation intervals (3, 4, and 5 days) and 1-farmer practice were used as control. The study result showed that 75% CROPWAT fixed depth at 3-day intervals achieved high water productivity, and saved 2873m3ha-1 of irrigation water compared with farmers’ method of irrigation. It provides additional irrigated land of 0.84 ha with a yield gain of 10.44 t ha-1. Therefore, a 3-day irrigation interval with 75% CROPWAT irrigation depth was recommended for the optimum yield and water productivity of the crop.